Ionic Liquids and Deep Eutectic Solvents for Enhanced Delivery of Antibodies in the Gastrointestinal Tract. (29th June 2020) - Angsantikul, Pavimol; Peng, Kevin; Curreri, Alexander M.; Chua, Ye; Chen, Kevin Z.; Ehondor, Jessica; Mitragotri, Samir
Abstract: Monoclonal antibodies (mAbs) are currently used for the treatment of numerous conditions including cancer, psoriasis, arthritis, and atopic dermatitis, among others. All mAbs are currently administered by either intravenous or subcutaneous injections. Herein, the use of a novel ionic liquid and deep eutectic solvent, choline and glycolate (CGLY), as a platform for gastrointestinal administration of therapeutic antibodies is reported. CGLY maintains the stability and structure of TNFα antibody. CGLY significantly enhances paracellular transport of TNFα antibody in vitro. CGLY also reduces the viscosity of the intestinal mucus, another key barrier for antibody transport. In vivo results in rats demonstrate that CGLY effectively delivers TNFα antibody into the intestinal mucosa as well as systemic circulation. One week repeat dose study followed by histology and serum biochemistry analysis indicates that CGLY is well tolerated by rats. Overall, this work illustrates the promise of using choline‐based ionic liquids and deep eutectic solvents as an oral delivery platform for local as well as systemic delivery of therapeutic antibodies. Abstract : A novel ionic liquid and deep eutectic solvent is reported for oral delivery of monoclonal antibodies (mAbs). The choline glycolate (CGLY) shows great compatibility with mAbs. In vivo studies indicate that CGLY has superior mAbs delivery into the intestinal epithelia and systemic circulation. The enhanced delivery is attributed to CGLY's ability to improve paracellular transport and reduce intestinal mucus viscosity.